Infective Endocarditis by Yersinia Species: A Systematic Review - Petros Ioannou; Georgios Vougiouklakis; Stella Baliou; Eugenia Miliara; Diamantis P. Kofteridis (Tropical Medicine and Infectious Disease, 2021)
Yersinia spp. are non-spore-forming Gram-negative bacilli. They comprise only three species known to cause disease in humans, namely Y. pestis, Y. enterocolitica and Y. pseudotuberculosis. Since infective endocarditis (IE) is rarely caused by Yersinia, the management of these infections can be problematic due to the lack of experience. The purpose of this study was to systematically review all published cases of IE by Yersinia species in the literature. A systematic review of PubMed, Scopus and Cochrane Library (through 1 November 2020) for studies providing epidemiological, clinical and microbiological information as well as data on treatment and outcomes of IE caused by Yersinia species was performed. A total of 12 studies, containing data of 12 patients, were included. A prosthetic valve was present in 17% of patients. The mitral valve was the most commonly infected site, followed by the aortic valve. Fever, sepsis and embolic phenomena were common clinical signs, followed by heart failure. Aminoglycosides, cephalosporins and quinolones were the most commonly used antimicrobials. Clinical cure was noted in 83%, while overall mortality was 17%. This systematic review describes IE by Yersinia and provides information on patients’ epidemiology, clinical signs and the related therapeutic strategies and outcomes.